Neurocysticercosis: a Review into Treatment Options, Indications, and Their Efficacy - Hamamoto Filho, Pedro Tadao [UNESP] (2022)
Neurocysticercosis, due to the localization of Taenia solium larvae in the Central Nervous System, is a neglected tropical disease still endemic in much of Latin America, Asia and sub-Saharan Africa. The therapeutic management of NC has gradually improved with the establishment of neuroimaging studies (CT and MRI) in endemic countries and with the demonstration of the efficacy of albendazole and praziquantel in the 1980s. But the morbidity and mortality of this preventable disease remain an unacceptable fact. In this scoping review, we will revise the different treatment options and their indications.